Modelling the determinants of the business performance of small and micro accommodation enterprises in the formal sector in South Africa - Van Zyl, Hendrik Johannes Christoffel (Stellenbosch : Stellenbosch University, 2017)
Thesis (PhD)--Stellenbosch University, 2017.